MINI-REVIEW: GREEN ROOF AS A GREENERY SOLUTION IN URBANIZED SETTLEMENTS AND ENERGY SAVING IN BUILDINGS - Rustam Efendi; Yohanna Anisa Indriyani (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2022)
Dense population and limited land for greenery are major problems in urban areas. Air pollutions and uncomfortable temperature of rooms are also problems in urban areas. Utilization of air conditioning for cooling the room in fact requires a lot of energy and also triggers other environmental problems, such as global warming. One of the efforts can be done is to green the roof, called green roof. Green roof is a method of planting on the roof, serves to isolation the heat and help maintaining plant biodiversity. Plants generally grown on green roof are ornamental plants and some species of plants that have large roots. The selection of plants must receive great consideration because they are adjusted to the ability of the roof on each building. Green roofs are also a step towards green energy, to reduce excessive use of energy and minimize environmental problems. This paper reviews the development of green roofs, where green roofs have been considered as solution to environmental and energy problems.